ASSESSMENT OF THE EFFICIENCY OF REALIZING THE POTENTIAL OF AGRICULTURAL VARIETY IN THE NORTH CAUCASUS FEDERAL DISTRICT - E. Kriulina (Вестник Северо-Кавказского федерального университета)
The article analyzes the results of the socio-economic development of the subjects of the North Caucasian Federal District (NCFD) and identifies the conditions that form their differentiation in terms of economic, demographic, social andfinancial results. The article provides an assessment of the main socioeconomic results of management by the level of asymmetry, polarization, and oscillation indicators that characterize their unevenness. It has been established thatfor the effective implementation of the potential of diversity and the use of the resources of the agrarian family-individual business of the subjects of the North Caucasus Federal District, targeted supportfrom government structures and businesses and a reassessment of the mutual influence of the level of development of agricultural production and rural areas are required.